Drug-Induced Severe Cutaneous Adverse Reactions: Insights Into Clinical Presentation, Immunopathogenesis, Diagnostic Methods, Treatment, and Pharmacogenomics - Tempark, Therdpong; John, Shobana; Rerknimitr, Pawinee; Satapornpong, Patompong; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2022)
SCARs are rare and life-threatening hypersensitivity reactions. In general, the increased duration of hospital stays and the associated cost burden are common issues and in the worst-case scenario, they can result in mortality. SCARs are delayed T cell-mediated hypersensitivity reactions. Recovery can take anywhere from 2 weeks to many months after dechallenging the culprit drugs. Genetic polymorphism of the HLA genes may change the selection and presentation of antigens, allowing toxic drug metabolites to initiate immunological reactions. However, each SCAR has a different onset latency period, clinical features, or morphological pattern. This explains other than HLA mutations, other immunopathogenesis may be involved in drug-induced severe cutaneous reactions. This review will discuss the clinical morphology of various SCARs, various immune pathogenesis models, diagnostic criteria, treatments, the association of various drug-induced reactions and susceptible alleles in different populations, and the successful implementation of pharmacogenomics in Thailand for the prevention of SCARs.